Penurunan Kadar Mikroplastik Tipe Serat Pada Limbah Laundry Dengan Metode Elektrokoagulasi - Putri Nur Rizkia; Novirina Hendrasarie (Fakultas Teknik, 2022)
Increased levels of fiber-type microplastics in waters caused by waste can disrupt the ecosystem in the water and human life. Fiber type microplastics with a size of 3 nm-15 mm, have hydrophobic properties that can bind harmful substances such as Dichloro Diphenyl Trichloroethan (DDT). There is one treatment that can be used to reduce microplastics by electrocoagulation process. This research was run to determine the effectiveness of reducing the levels of fiber-type microplastics by electrocoagulation processing and aluminium as the electrodes, as well as the flocculation coagulation process with PAC coagulant as a control variable. electrocoagulation process with a current of 6 Ampere; 7 Ampere; 8 Ampere; and 9 Ampere. From the research, it was found that the most effective variation of current was 6 Ampere with a removal percentage of 90% with a zeta potential value of +0.421 mV. The research using the coagulation-flocculation process with PAC coagulation at a dose of 46.4 mg/l with a stirring speed during coagulation of 400 rpm for 0.5 and flocculation of 40 rpm for 20 minutes and a decrease of 30 minutes, decreased levels of microplastic 71% with a zeta potential value of -7,5 mv.